Proposal to optimize evaluation and treatment of Febrile infection‐related epilepsy syndrome (FIRES): A Report from FIRES workshop. Issue 1 (13th January 2021) - Koh, Sookyong; Wirrell, Elaine; Vezzani, Annamaria; Nabbout, Rima; Muscal, Eyal; Kaliakatsos, Marios; Wickström, Ronny; Riviello, James J.; Brunklaus, Andreas; Payne, Eric; Valentin, Antonio; Wells, Elizabeth; et al.
Abstract: Febrile infection‐related epilepsy syndrome (FIRES) is a rare catastrophic epileptic encephalopathy that presents suddenly in otherwise normal children and young adults causing significant neurological disability, chronic epilepsy, and high rates of mortality. To suggest a therapy protocol to improve outcome of FIRES, workshops were held in conjunction with American Epilepsy Society annual meeting between 2017 and 2019. An international group of pediatric epileptologists, pediatric neurointensivists, rheumatologists and basic scientists with interest and expertise in FIRES convened to propose an algorithm for a standardized approach to the diagnosis and treatment of FIRES. The broad differential for refractory status epilepticus (RSE) should include FIRES, to allow empiric therapies to be started early in the clinical course. FIRES should be considered in all previously healthy patients older than two years of age who present with explosive onset of seizures rapidly progressing to RSE, following a febrile illness in the preceding two weeks. Once FIRES is suspected, early administrations of ketogenic diet and anakinra (the IL‐1 receptor antagonist that blocks biologic activity of IL‐1β) are recommended.